Can Incidental Vascular Calcifications at Mammography be Used as a Screening Biomarker for Heart and Kidney Disease?. (March 2019) - Erbil, Damla; Onal, Emine M.; Demirel, Cagri; Sag, Alan A.; Dagel, Tuncay; Afsar, Baris; Covic, Adrian; Kanbay, Mehmet
Mammography is a screening test with extensive international application and financial infrastructure promoting accessibility and affordability. Designed specifically to detect microcalcifications, mammography is powered to detect calcifications in vessel walls. Breast arterial calcifications (BAC) are one of the most common incidental findings documented by mammography. This review considers the literature regarding BAC in relation to cardiovascular disease (CVD) and its risk factors. The aim is to assess the possibility of using BAC as an early surrogate imaging biomarker of CVD.